ナンキョク ショウワキチ ダイ10 キョジュウトウ モクシツ ザイリョウ ノ ザンゾン キョウド - 平居, 孝之; ヒライ, タカユキ; 平山, 善吉; ヒラヤマ, ゼンキチ; 大谷, 俊浩; オオタニ, トシヒロ; 松田, 忠広; マツダ, タダヒロ; Hirai, Takayuki; Hirayama, Zenkichi; Otani, Toshihiro; Matsuda, Tadahiro (2002)
P(論文) 建設後29年経過した南極昭和基地の第10居住棟と建設後31年経過した放球棟で使用されていた木質パネル枠材の残存強度を調べた。木質枠材にねじ込んだビスを引き抜いたときの強度を同じ材質の新材について、強度と気乾密度の関係を前もって測定した数値と比較して木質枠材の強度を表した。この関係を用いて、木質枠材の強度の測定結果から強度残存率を評価した。その結果木質枠材の強度の低下は小さいと考えられた。 The remaining strength of wooden frames in the panels used in the old living hut built in 1969 at Syowa Station in Antarctica, which is 29 years old, and that in the balloon-launching building, which is 31 years old, were examined. The pulling out strength of the nail screwed into the wooden frames was used to measure the strength of the wooden frames. The relation between the strength of virgin wood of the same kind as wooden frames and its air dried specific gravity was measured by preliminary test. The ratio of the remaining strength against the initial strength of the virgin wood was estimated from the strength of wooden frames using the result of the preliminary test. It is concluded that the strength of the wooden frames deterorated little. departmental bulletin paper